Shatterproof [compact disc, unabridged] - Smith, Roland, 1951- (39 clues. Cahills vs. Vespers, 2012)
After pulling some spectacular heists, Amy and Dan have become two of Interpol's most wanted criminals. So when Vesper One orders them to steal the world's largest diamond, they know they're facing life in prison, or worse. With the Cahill hostages still in peril, Amy and Dan have no choice but to launch a mission that leads them to an ancient city full of dangerous secrets.